2003
DOI: 10.1037/1040-3590.15.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Personality Questionnaire profiles of veterans with traumatic combat exposure: Externalizing and internalizing subtypes.

Abstract: This study used the Multidimensional Personality Questionnaire (MPQ; A. Tellegen, in press) to identify personality-based subtypes of posttraumatic response. Cluster analyses of MPQs completed by combat veterans revealed subgroups that differed on measures relating to the externalization versus internalization of distress. The MPQ profile of the externalizing cluster was defined by low Constraint and Harmavoidance coupled with high Alienation and Aggression. Individuals in this cluster also had histories of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
183
8
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 179 publications
(223 citation statements)
references
References 57 publications
31
183
8
1
Order By: Relevance
“…The factors scores were correlated, but only the externalizing factor was uniquely related to self-report of aggression over the past year. Though previous research has provided support for applying an internalizing/externalizing distinction to understanding heterogeneity in the presentation of patients with PTSD (Miller, 2003;Miller et al, 2003Miller et al, , 2004Miller et al, , 2008Miller et al, , 2012, to our knowledge this is the first report to (1) assess the internalizing/externalizing dimensions of posttraumatic stress and associated comorbidity as measured by the PAI and (2) demonstrate the incremental contribution of externalizing psychopathology in the measurement of aggressive behavior.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The factors scores were correlated, but only the externalizing factor was uniquely related to self-report of aggression over the past year. Though previous research has provided support for applying an internalizing/externalizing distinction to understanding heterogeneity in the presentation of patients with PTSD (Miller, 2003;Miller et al, 2003Miller et al, , 2004Miller et al, , 2008Miller et al, , 2012, to our knowledge this is the first report to (1) assess the internalizing/externalizing dimensions of posttraumatic stress and associated comorbidity as measured by the PAI and (2) demonstrate the incremental contribution of externalizing psychopathology in the measurement of aggressive behavior.…”
Section: Discussionmentioning
confidence: 85%
“…VA Author Manuscript on internalizing or externalizing behavior (see, e.g., Forbes et al, 2010;Miller, Greif, & Smith, 2003;Miller, Kaloupek, Dillon, & Keane, 2004;Miller & Resick, 2007). While these studies have supported the internalizing/externalizing distinction as a useful heuristic for studying the structure of posttraumatic psychopathology, they are limited by a reliance on cluster-analytic models which are not optimal for examining higher order factor structure of psychopathology thought to be dimensional (Miller, Fogler, Wolf, Kaloupek, & Keane, 2008).…”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…In that study, Allen, Huntoon, and Evans (1999) performed cluster analyses on Millon Clinical Multiaxial Inventory-III (Millon, 1994) personality disorder scale data obtained from an inpatient sample of women with "severe trauma-related disorders." Their analyses revealed a five-cluster solution that bore close resemblance to the subgroups more recently described by Miller et al (2003Miller et al ( , 2004. Two clusters, labeled by Allen et al as "alienated" and "aggressive," resembled externalizers and showed elevated scores on measures of anger, aggression, antisocial and borderline personality disorder, alcohol dependence, drug abuse, and mania.…”
Section: Subtypes Of Complex Ptsd?mentioning
confidence: 76%
“…In both studies, a third lower pathology cluster was characterized by normal range personality scale scores along with relatively few comorbid diagnoses. Miller et al (2003Miller et al ( , 2004 hypothesized that the qualitative differences between these subgroups reflect the influence of personality on core psychopathological processes thought to be fundamental to the structure and organization of mental disorders broadly (Achenbach & Edelbrock, 1978, 1984Kendler, Prescott, Myers, & Neale, 2003;Krueger, Caspi, Moffitt, & Silva, 1998;Krueger, McGue, & Iacono, 2001) and the form and expression of posttraumatic responses more specifically.A major limitation of this work was the exclusive focus on male combat veterans, which left open questions about the generalizability of the findings to other populations of trauma survivors. Thus, the primary objective of this study was to examine whether similar subtypes would be found among a sample of women with PTSD.…”
mentioning
confidence: 99%
“…In a study of veterans receiving services at a VA PTSD clinic, Miller et al. reported the reliability of GAF ratings assessed by two different raters within 30 days (e.g., a combined test-retest and interrater reliability index) to be 0.55 [10]. These investigators also reported a significant negative association between the severity of posttraumatic psychopathology and GAF scores.…”
Section: Introductionmentioning
confidence: 99%